Prevalence of Schizophrenia in Idiopathic Normal Pressure Hydrocephalus. Issue 4 (8th May 2018) - Vanhala, Vasco; Junkkari, Antti; Korhonen, Ville E; Kurki, Mitja I; Hiltunen, Mikko; Rauramaa, Tuomas; Nerg, Ossi; Koivisto, Anne M; Remes, Anne M; Perälä, Jonna; Suvisaari, Jaana; Lehto, Soili M; et al.
Abstract: BACKGROUND: Idiopathic normal pressure hydrocephalus (iNPH) is a progressive and potentially treatable neurodegenerative disease affecting elderly people, characterized by gait impairment and ventricular enlargement in brain imaging. Similar findings are seen in some patients with schizophrenia (SCZ). OBJECTIVE: To determine the prevalence of SCZ among patients suffering from probable or possible iNPH and the specific effects of comorbid SCZ on the outcome of the cerebrospinal fluid (CSF) shunting. METHODS: All medical records of the 521 iNPH patients in the NPH registry were retrospectively analyzed from 1991 until 2017. The prevalence of comorbidity of SCZ was determined and compared to that of general aged (≥65 yr) population in Finland. RESULTS: We identified a total of 16 (3.1%) iNPH patients suffering from comorbid SCZ. The prevalence of SCZ among the iNPH patients was significantly higher compared to the general population (3.1% vs 0.9%, P < .001). All iNPH patients with comorbid SCZ were CSF shunted and 12 (75%) had a clinically verified shunt response 3 to 12 mo after the procedure. The CSF shunt response rate did not differ between patients with and without comorbid SCZ. CONCLUSION: SCZ seems to occur 3 times more frequently among iNPH patients compared to the general aged population in Finland. The outcome of the treatment was not affected by comorbid SCZ and therefore iNPH patients suffering from comorbid SCZ should not be left untreated. These results merit validation in other populations. In addition, further research towards the potential connection between these chronic conditions is warranted.